Association of regional cerebral oxygen saturation and postoperative pulmonary complications in pediatric patients undergoing one-lung ventilation: A propensity score matched analysis of a prospective cohort study - Li, Shanshan; Zhang, Jianmin; Hu, Jing; Li, Lijing; Liu, Guoliang; Zheng, Tiehua; Wang, Fang; Liu, Lin; Li, Gan (Frontiers in Pediatrics, 2022)
Abstract Background: Previous studies of the relationship of regional cerebral oxygen saturation (rScO2) and postoperative pulmonary complications (PPCs) in pediatric patients are not well established, and further investigation is warranted. The aim of this prospective study was to determine whether a decrease in intraoperative rScO2 is associated with PPCs in children undergoing thoracoscopic surgery requiring one-lung ventilation (OLV). Methods: One hundred and six children of ages 3 months to 8 years who received one-lung ventilation were enrolled in the study. Upon entering the operating room, regional cerebral oxygen saturation was continuously monitored bilaterally by near-infrared spectroscopy. Patients were divided into low rScO2 (L-rScO2) or high rScO2 (H- rScO2) groups according to whether the lowest intraoperative rScO2 value was 15% lower than the baseline value. Outcome is defined as PPCs occurring within 7 days after surgery. Results: After propensity score matching, 23 pediatric patients with decreased rScO2 and 46 pediatric patients without a decrease in rScO2 were included in this study. According to logistic regression analysis, patients in the H- rScO2 group were less likely to have PPCs than those in the L-rScO2 group (OR=3.16; 95% CI=1.05-9.5; P=0.04). Moreover, intraoperative rScO2 reduction was associated with an increase in the severity of PPCs (OR=3.90; 95% CI=1.19-12.80; P=0.025). Conclusions: The decrease in regional cerebral oxygen saturation during surgery increases the likelihood of postoperative pulmonary complications.